13th International Public Communication of Science and Technology. Mayo 5 al 8, 2014, Salvador, Brasil. (2014)
In Colombia there is a noticeable difference, between public and private schools, in the approach and education of science, leaving the students of the former ones at a disadvantage. As a response to that, the EAFIT Children’s University program has been proposed to promote inclusion and social integration through the following process: every year 750 free places are assigned - 50% to public schools students and 50% to private schools students. With such methodology we acknowledge and value the diversity of the workshop´s participants, in terms of gender, social, cultural or family origins. But, how do these differences influence the approach to science and the collective building of knowledge? What kind of dilemmas appears due to the diverse origins of the participants? What knowledge have we acquired? What meaningful experiences have been collected that really lead to an understanding of how the diversity has a direct influence on the approach to and appropriation of science? In order to address those questions, we will present a case study with a group of 23 boys and girls between the ages of 7 and 8 years old, during 8 workshops that took place over the course of one year.